Urgensi Fatwa DSN-MUI Mengenai Manajemen Risiko Pembiayaan Berbasis Syariah - Tri Hidayati; Muhammad Syarif Hidayatullah (Al-Manahij: Jurnal Kajian Hukum Islam, 2021)
Risk management at Islamic financial institutions is still implementing bank Indonesia (BI) and Financial Services Authority (OJK) policies which previously applied the same to conventional financial institutions. The perfection of the enforcement of sharia principles in sharia financing institutions is not enough only in the aspect of transactional mechanisms, it needs to be supported by a sharia-based risk management system. The focus of this research includes the characteristics of Islamic financing, juridical aspects in the principle of prudence, and an overview of the maslahah of the urgency of sharia-based risk management. This research is normative legal research using a statutory approach and a benefits approach with a qualitative descriptive analysis. The results of the discussion show that a dynamic system also needs to be supported by juridical aspects to provide the legal force with the realization of regulatory solidity. At this regulatory level, in addition to the regulations issued by the OJK, the DSN-MUI fatwa is also very necessary and has a very urgent position. Because financing risk management is also part of the sharia economy that must maintain sharia principles, lest the application of sharia principles only exists in product technicalities, but does not apply to technical risk management. The expected sharia is the application of total sharia principles (kaffah), not partial ones.